Indigenous data sovereignty in higher education: Towards a decolonised data quality framework - Wilks, J.; Kennedy, G.; Wilson, Katie; Drew, N. (Nteu, 2018)
In the Australian higher education sector, the challenges to successful engagement and retention experienced by Aboriginal and/or Torres Strait Islander students and communities are considerable. They persist despite many well-intentioned attempts to address this issue and to strengthen equity in participation in the sector. Implicated in this is the absence of a culturally-informed data quality framework for the sector, and the resulting persistence of associated issues such as confusion with data ownership; consistency; standards; usage; and storage. In this paper we argue it is essential that rigorous inquiry be carried out into the type and nature of data required or sought in the higher education sector on, for and with Aboriginal and Torres Strait Islander peoples. This inquiry must involve Aboriginal and Torres Strait Islander educators, researchers, evaluators and communities to bring into effect their aspirations for data sovereignty including stewardship and ownership of data, and for culturally beneficial outcomes relating to the use and application of data. It also mandates a collaborative approach with existing government and independent organisations, and Indigenous and non-Indigenous researchers from higher education institutions, working together towards the development and implementation of an agreed-upon and decolonised Indigenous data framework for the sector. [Author abstract]